Caracterización mineralógica de los corindones de mercaderes, cauca (colombia) (2002)
The corundum mines of Colombia are located in the southern part of the Cordillera Central, specifically in the Mercaderes - Rio Mayo region. These corundum occurrences are found in the alluvial deposits of the Rubi, Guabo, Paloverde, Limoncito, Chenequeta, Cocal, Monteoscuro, Monserrate and Honda streams, where the material from the Granatifera Tuff is eroded. The corundums show surface features indicating transport, corrosion and mechanical abrasion. These materials are not likely to be cogenetic with the lamprophyric host, but are possibly crustal fragments accidentally incorporated into the eruption magma. The presence of rutile and almandine - pyrope as crystalline inclusions within the corundums, and the existence of augite, kyanite and hercynite suggest a metamorphic origin possibly associated with the granulite xenoliths found in the Granatífera Tuff.